2019
DOI: 10.17513/vaael.774
|View full text |Cite
|
Sign up to set email alerts
|

Market of Organic Agricultural Food Products in Russia

Abstract: Органическая сельскохозяйственная продукция, производство сельскохозяйственной органической продовольственной продукции, продовольственный рынок сельскохозяйственной органической продукции, правовое регулирование производства и реализации органической продукции; государственная поддержка, экономический механизм.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The development of organic agriculture involves the study of the functioning of the agricultural organic products` food market. [6,7,8]. Conducted research in this area revealed the following patterns.…”
Section: The Results Of the Studymentioning
confidence: 99%
“…The development of organic agriculture involves the study of the functioning of the agricultural organic products` food market. [6,7,8]. Conducted research in this area revealed the following patterns.…”
Section: The Results Of the Studymentioning
confidence: 99%
“…For example, the factors "Presence of an extensive network of roads" and "Presence of several industrial enterprises" are often positioned as positive (in SWOT analyzes they are indicated as strong points), since the road network allows building a logistics chain from a manufacturer to a processing plant or direct consumer, and large industrial enterprises or many small (medium) guarantee income and employment of the population, as well as replenishment of the budget, including through tax splitting. However, when agricultural producers plan to develop a system for growing organic products in a given area, these factors can become limiting due to large traffic flows and emissions during production processes, which leads to a high concentration of exhaust gases, heavy metals, toxic gases in the atmosphere, water resources and soil [18].…”
Section: Table 1 Project Model For the Renewal Of Rural Territoriesmentioning
confidence: 99%